Factors influencing investor decision making towards investing in shariah compliant securities in Malaysia / Muhammad Rafiuddin Mohd Razif and Nur Izzati Shahrel - Mohd Razif, Muhammad Rafiuddin; Shahrel, Nur Izzati (Faculty of Business and Management, 2014)
The decision making process is a cognitive process which results in the selection of a course of action among several alternatives. Every decision-making process produces a final choice. The output can be an action or an opinion of choice. Investment decisions made today often are critical for financial security in later life, due to the potential for large financial loss and the high costs of revising or recovering from a wrongful investment decision. Most of the equity investors or also known as retail investor do not have the sufficient knowledge of basic economic concepts required to make investment decisions. Therefore, this research is to find out what factors that make investors select shariah compliant securities as the statistics show in increasing over the year. To identify these factors the current study has applied factor analysis.